PENGARUH OPINI GOING CONCERN, REPUTASI KAP,AUDIT TENURE, PERGANTIAN MANAJEMEN TERHADAP AUDITOR SWITCHING DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Periode 2011- 2014) - Ria Erinda Putri; Yunieta Aniesma; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to investigate the influence of the going-concern opinion, the reputation of KAP, audit tenure, change of management of the auditor switching with financial distress as a moderating variable. The population in this research is manufacturing companies listed on the Stock Exchange during the period 2011-2014. The data used in this research is secondary data. The collection of data by the method of documentation, which is a means used to obtain data in the form of annual reports published by the companies sampled in the period 2014 on the website of the Stock Exchange (www.idx.co.id) by tracking the company's annual report were selected to be sampled research. As a guide then use the check-list or a list of questions yangt contains items responsibility disclosure sosial.Metode analysis of this study using logistic regression analysis using SPSS version 17.0. The results of this study indicate that the independent variables ie going concern opinion, audit tenure, management turnover significantly influence the auditor switching on the level (α)> 0.05, whereas KAP's reputation does not significantly influence the auditor switching on the level (α) <0.05 , Results ajusted R-Square-test of independent variables on the dependent variable was 49.3%. While the remaining 50.7% is influenced by other variables not examined in this study.Keywords: going concern, reputation KAP, audit tenure , distress, and switching